2013
DOI: 10.1007/s10120-013-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic total gastrectomy with D1+beta lymph node dissection for proximal early gastric cancer

Abstract: Single-incision laparoscopic distal gastrectomy for early gastric cancer has recently been reported by a few centers in Korea and Japan. In this technical report, we describe the world's first pure single-incision laparoscopic total gastrectomy with D1?beta lymph node dissection for proximal early gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…They started pure single-incision laparoscopic distal and total gastrectomy for early gastric cancer in November 2012 [7]. In some cases, we have encountered the need for D2 LND because of unexpected LN enlargement that may be present even in early-stage gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They started pure single-incision laparoscopic distal and total gastrectomy for early gastric cancer in November 2012 [7]. In some cases, we have encountered the need for D2 LND because of unexpected LN enlargement that may be present even in early-stage gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A 10-mm flexible high-definition scope (Endoeye flexible HD camera system, Olympus Medical Systems Co., Tokyo, Japan), a Harmonic Scalpel (Ethicon Endo-Surgery Inc., Cincinnati, OH, USA), and a LigaSure 5-mm Blunt Tip (Covidien, Mansfield, MA, USA) were used to visualize nearly the same field as that observed in conventional laparoscopic gastrectomy and to facilitate dissection and bleeding control. The detailed procedures, including a modified combined suture retraction of the liver, partial omentectomy, and LND for LNs 6, 5, 12a, 8a, and 7, have been described in our previous reports [7]. …”
Section: Surgical Techniquementioning
confidence: 99%
“…The case report of pure single incision total gastrectomy for proximal early gastric cancer was firstly reported in 2014 (50). Collision of each instrument is expected to be more serious and making good surgical field also more difficult, however authors reported similar operation outcome compared to conventional multiport laparoscopic total gastrectomy.…”
Section: Single Incision Total Gastrectomymentioning
confidence: 99%
“…Ahn et al 45 and Ertem et al 46 reported several patients who successfully underwent single-port LTG (Table 5). The surgical outcomes of single-port LTG were not significantly different from those of dual-port LTG or conventional LTG.…”
Section: Dual-port or Single-port Ltgmentioning
confidence: 99%